2012
DOI: 10.3233/bd-2012-000337
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory breast cancer in North Africa: Comparison of clinical and molecular epidemiologic characteristics of patients from Egypt, Tunisia, and Morocco

Abstract: Understanding molecular characteristics that distinguish inflammatory breast cancer (IBC) from non-IBC is crucial for elucidating breast cancer etiology and management. We included 3 sets of patients from Egypt (48 IBC and 64 non-IBC), Tunisia (24 IBC and 40 non-IBC), and Morocco (42 IBC and 41 non-IBC). Egyptian IBC patients had the highest combined erythema, edema, peau d'orange, and metastasis among the 3 IBC groups. Egyptian IBC tumors had the highest RhoC expression than Tunisians and Moroccan IBCs (87% v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 33 publications
1
27
2
Order By: Relevance
“…In a French study, we note that IBC patients are less obese, and only 21% of patients presented high BMI [ 12 ]. Furthermore, results from a comparative study between North-African series show no significant difference in BMI between IBC and non-IBC patients, but the authors still insist on the need for further studies because of the increasing incidence of obesity among women in North Africa [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a French study, we note that IBC patients are less obese, and only 21% of patients presented high BMI [ 12 ]. Furthermore, results from a comparative study between North-African series show no significant difference in BMI between IBC and non-IBC patients, but the authors still insist on the need for further studies because of the increasing incidence of obesity among women in North Africa [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Compared to the 2% incidence, IBC accounted for 7% (1936/27747) of mortality for all breast cancer, so the mortality rate of IBC was significantly higher than other types of breast cancer 9 . The incidence of IBC has a large geographical difference with a 2% incidence in China 10 , and a 6-10% incidence in the countries of North Africa, particularly in Morocco, Algeria, Tunisia, and Egypt 11 . Robertson et al 12 reported that the five-year survival rate of the patients with IBC was less than 5% when treated with single surgical resection or chemotherapy.…”
Section: Clinical Characteristics and Epidemiological Profile Of Ibcmentioning
confidence: 99%
“…These symptoms along with blockage of lymphatic vasculature cause swelling of the breast, hence the name IBC. Epidemiologic studies have indicated that IBC is a heterogeneous disease [7, 8]. The expression of molecular markers in IBC differs depending on patient population; for example, Egyptian IBC patients have higher expression of RhoC GTPase than do patients from Tunisia, Morocco, and the USA [7, 8].…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiologic studies have indicated that IBC is a heterogeneous disease [7, 8]. The expression of molecular markers in IBC differs depending on patient population; for example, Egyptian IBC patients have higher expression of RhoC GTPase than do patients from Tunisia, Morocco, and the USA [7, 8]. Conventional therapies (surgery, radiation, chemotherapy) alone or in combination are less effective against IBC than other breast cancers with the 3-year relative survival rate being only 42 % as compared to 85 % [1].…”
Section: Introductionmentioning
confidence: 99%